Malignant Clinical Presentation of a Benign Granular Cell Tumor of Breast in a Patient with Previously Treated Contralateral Invasive Ductal Carcinoma. (29th November 2012) - Tural, Deniz; Akar, Emre; Öztürk, Tülin; Turna, Hande; Serdengeçti, Süheyla
Abstract : GCT is a rare neoplasm and usually shows the benign character. GCT can occur in any body site and may be multifocal. The most common involved site is tongue which accounts for nearly 30% of all cases but skin and subcutaneous tissue are also affected frequently. Breast is an unusually involved site and accounts for 6% of all GCTs. The histiogenesis of GCT is still controversial but further investigations and immunohistochemical examinations were exposed to neural origin and the tumor is thought to be derived from Schwann cells of peripheral nerves. Generally used technique to diagnose GCT is the positivity of S-100 immunohistochemical staining. Despite its benign nature, GCT may mimic breast carsinoma clinically and radiologically and easily be misdiagnosed for breast cancer. We herein report a case of granular cell tumor that arose in a 56 year-old female patient who previously had been treated from an invasive ductal carcinoma in contralateral breast.